Role and regulation of the orphan AphA protein of quorum sensing in pathogenic Vibrios. (March 2018) - Lu, Renfei; Osei-Adjei, George; Huang, Xinxiang; Zhang, Yiquan
Quorum sensing (QS), a cell-to-cell communication process, is widely distributed in the bacterial kingdom. Bacteria use QS to control gene expression in response to cell density by detecting the signal molecules called autoinducers. AphA protein is the master QS regulator of vibrios operating at low cell density. It regulates the expression of a variety of genes, especially those encoding virulence factors, flagella/motility and biofilm formation. The role and regulation of AphA in vibrios, especially in human pathogenic vibrios, are summarized in this review. Clarification of the roles of AphA will help us to understand the pathogenesis of vibrios.